THE EFFECT OF READING TO LEARN (R2L) MODEL ON SCIENCTIFIC LITERACY OF LIVING THINGS CLASSIFICATION LEARNING MATERIALS - Putri, Elmesa; Oktavia, Rani; Arif, Khairil; Muttaqiin, Arief (Pendidikan IPA, FMIPA, UNP, 2024)
This study aims to determine the effect of R2L model on scienctific literacy competence of students on the classification of Living Things learning material. The type of this research is a quasi experiment with nonequivalent control group design. This research was conducted in the 7th grade of SMPN 7 Payakumbuh, West Sumatra. The sampling was taken by purposive sampling technique to get 32 students of class VII.I as experimental group and 23 students of class VII.II as control group. The instrument used is a test of science literacy questions as many as 16 questions with 3 forms of questions. The results showed that the use of the R2L model increase the science literacy competence of students. The important syntax in supporting the improvement of students' scientific literacy competence is at the detailed reading and note-making stages. This stage allows students to read the reading text attentively and find important words in the text.